The influence of compost humic acid quality and its ability to alleviate soil salinity stress - S. El hasini; M. De Nobili; M. El. Azzouzi; K. Azim; A. Douaik; M. Laghrour; Y. El idrissi; M. El alaoui El belghiti; A. Zouahri (International Journal of Recycling of Organic Waste in Agriculture)
Purpose Soil salinization is one of the most severe abiotic stresses which threaten sustainable agriculture in arid and semi-arid regions including Morocco. The application of organic amendments like composts to saline soils has been confirmed to alleviate soil salinity stress. The present work aims to study the effect of humic acids (HA), as one of the products resulting from organic matter decomposition, on soil salinity reduction. Methods In this perspective, four composts made from mixtures corresponding to initial C/N ratios of 25, 30, 35 and 40 were tested. The four composts were made from mixtures of different proportions of greenhouse wastes, olive mill waste and sheep manure in Souss-Massa region. Representative samples underwent physicochemical analysis, extraction, purification and analysis of HA. The maturity of compost was assessed through some maturation index, prior to the main trial of the interaction between extracted HA and sodium carbonates salt (Na2CO3), largely encountered in saline soils. Results The results showed that the compost with initial C/N ratio of 35 is the most recommended for application as an amendment to alleviate soil salinity. Conclusion The salt stress alleviating effect of compost may be advocated to compost humic acids and their ability to chelate sodium on their carboxylic sites.